The universal shape of economic recession and recovery after a shock - Damien Challet; Sorin Solomon; Gur Yaari (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
We show that a simple and intuitive three-parameter equation fits remarkably well the evolution of the gross domestic product (GDP) in current and constant dollars of many countries during times of recession and recovery. We then argue that this equation is the response function of the economy to isolated shocks, hence that it can be used to detect large and small shocks, including those which do not lead to a recession; we also discuss its predictive power. Finally, a two-sector toy model of recession and recovery illustrates how the severity and length of recession depends on the dynamics of transfer rate between the growing and failing parts of the economy.
Keywords: C32; O23; O41; 330; Economic growth; GDP; shocks; response function; modelling; prediction; optimal policy